Carbonation of mantle peridotite by CO2-rich fluids: the formation of listvenites in the Advocate ophiolite complex (Newfoundland, Canada) - Menzel, Manuel D. (2018)
The mantle section of the Advocate ophiolite (Newfoundland, Canada) contains unique outcrops of listvenite (magnesite-quartz), antigorite- and quartz-bearing talc-magnesite rock, and carbonated antigorite-serpentinite. This lithological sequence records the sequential carbonation of serpentinite by CO2-rich hydrothermal fluids. High Cr and Ni contents and preservation of Cr-spinel with a composition similar to that of Atg-serpentinite (molar Mg/Mg + Fe = 0.50–0.65; Cr/Cr + Al = 0.50–0.70), show that the Advocate listvenite and talc-magnesite rocks formed by carbonation of variably serpentinized mantle harzburgite. Replacement of lizardite by magnesite coeval with the breakdown of lizardite to antigorite + brucite and the lack of prograde olivine and magnetite in antigorite serpentinite and talc-magnesite rocks constrain the temperature of carbonation between c. 280 °C and 420 °C. Thermodynamic modelling of carbonation of serpentinite at 300 °C and 0.2–0.5 GPa accounts for the sequence of carbonated rocks in the Advocate complex. Phase relations and petrological observations indicate that the aqueous aSiO2 and aCO2 of the infiltrating CO2-rich fluid were buffered at the Atg-Tlc-Mgs and Qtz-Tlc-Mgs pseudo-invariant points, forming dominantly three-phase rocks by variable extents of carbonation at these pseudo-invariant points. Listvenites formed at large fluid-rock ratio when quartz became saturated in the fluid and precipitated along magnesite grain boundaries and in variably sized tensional veins. The whole rock Fe3+/Fetotal ratio of the Advocate carbonate-bearing sequence decreases with increasing whole rock carbon content, from 0.65–0.80 in brucite-bearing antigorite serpentinite to 0.10–0.30 in talc-magnesite rocks and listvenite. The whole rock iron reduction is associated with an increase in the ferrous iron content of magnesite and the formation of hematite and goethite, indicating a concomitant increase of the fluid oxygen fugacity. The sequence of carbonation reactions is uniquely preserved in three main growth zones characteristic of listvenite magnesite: (i) an inner zone of magnetite-bearing, Fe-poor, Mn-bearing magnesite formed by carbonation of lizardite, brucite and olivine from Atg-serpentinite; (ii) an outer zone of Fe-rich magnesite formed by carbonation of antigorite and in equilibrium with Fe-poor talc; and (iii) an outermost rim of Fe-poor magnesite formed by carbonation of talc. We propose that carbonation of the Advocate serpentinized mantle harzburgite occurred in a supra-subduction upper plate ophiolite by fluxing of slab-derived, CO2-rich fluids channelled along deep faults at the onset of accretion of the forearc basin (c. 300 °C, <0.5 GPa). The rather constant δ18O (11.0–14.4‰ V-SMOW) and relatively low δ13C (−8.9 to −5.0‰ V-PDB) of magnesite throughout the sequence of carbonated rocks in the Advocate complex is consistent with CO2-rich fluids derived from decarbonation or dissolution of organic carbon- and carbonate-bearing meta-sediments, such as those occurring in the underlying Birchy complex — the partially subducted continental margin of Laurentia. Carbonation of serpentinized oceanic or continental mantle lithosphere by reactive percolation of CO2-rich fluids derived from the slab in forearc settings may represent a significant carbon reservoir for the deep carbon cycle.